When the land leaves: place, displacement, and climate mobilities in an era of climate change - Julia Bello-Bravo (Frontiers in Human Dynamics)
Reframing the notions of climate migration and climate-induced displacement as one type of involuntary climate mobility and human displacement, this conceptual review explores how disruptions to the relational and cultural coherence of person/place-attachments erode people’s ability to remain where they are. Offering a framework for complementing and refining technocratic adaptation and resilience strategies to redress such involuntary climate mobilities, it articulates a notion of stationary displacement to show how existential attachments to land, identity, and meaning can sustain local continuities when kept intact and how fraying those attachments contributes to a felt need to involuntarily move, especially in still largely land-based, traditional, and Indigenous societies. The aim of this review is not to replace existing efforts to mitigate or prevent involuntary climate mobilities but to strengthen and further ground them in people’s lived experiences of place so that staying becomes not only more possible but also more meaningful.